Understanding the Occupational Adaptation Process and Well-Being of Older Adults in Magallanes (Chile): A Qualitative Study - Palma Candia, Oskarina Carmen; Hueso Montoro, Cesar; Marti-Garcia, Celia; Fernandez-Alcantara, Manuel; Petra Campos-Calderon, Concepcion; Montoya Juarez, Rafael (My University, 2019)
Background: Aging and longevity are important topics nowadays. Purpose: To describe how older adults perform the occupational adaptation process in the extreme region of Magallanes (Chile), and to identify the factors that might contribute to successful occupational adaptation and well-being. Method: Qualitative study, with a phenomenological interpretative approach. In-depth interviews were carried out with 16 older adults, with high or low levels of well-being, assessed with the Ryff Scale. An inductive content analysis according to Elo and Kyngas was performed. Findings: Resilience, self-esteem and interdependence with significant others are key elements that promote well-being. Participants develop strategies to minimize the effects of environmental factors. The occupation's function in terms of socialization, use of time, and social participation is revealed as a conditioning factor of occupational adaptation. Implications: Interventions with older people to achieve a successful occupational adaptation process must take into consideration the commitment to meaningful activities.
Keywords: adaptation; psychological; aging; life change events